Crime of Inciting the Use of Narcotic or Pyschotropic Substances - (:unkn) unknown (ISTANBUL UNIV, FAC LAW, 2020)
Narcotic and psychotropic substances are stuffs that direct affect on the nervous system; drag to user and all society into the economic, social and moral collapses that difficult to cure, by creating physical and psychological addiction. The fact that the effects of these substances contained a major threat to the public health and it required the establishment of legal regulations on this issue. Therefore, narcotic and psychotropic substances were entered the criminal law's theme and various criminal offences have been introduced about them. According to the Turkish Criminal Code No. 5237, Article 190/2; inciting the use of these substances is considered a crime and imposed sanctions on this crime type leads to some discussions about penal protection of public health and fundamental rights and freedoms in public and law communities. First, in this study offence of inciting the use of narcotic or pyschotropic substances have been examined with framework of related law articles; then, mentioned above discussions were evaluated with related constitutional provisions, actual court decisions and informations about comparative law. Finally; substantive and procedural problems arising from the application of these rules were identified and possible solutions were proposed in this study.
Keywords: Narcotic and psychotropic substances; Inciting the use of narcotic or pyschotropic substances; Public health; Freedom of science and art